2015
DOI: 10.1007/s00784-015-1681-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of malocclusions on oral health-related quality of life in children—a systematic review and meta-analysis

Abstract: IntroductionA limited amount of systematic literature reviews on the association between malocclusions and oral health-related quality of life (OHRQOL) summarize inconclusive results. Therefore, we conduct a systematic review and meta-analysis on the association of malocclusions with OHRQOL in children.MethodsRelevant studies were identified in Pubmed, Embase, Cochrane, Google Scholar and other databases. All studies with data on malocclusions or orthodontic treatment need and OHRQOL in children were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
173
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 66 publications
(103 reference statements)
8
173
0
9
Order By: Relevance
“…Regarding the occlusal traits, we observed that the increased overjet had a negative impact on the quality of life of 5‐year‐old children independent of the presence of remaining clinical and demographic variables. A recent systematic review concluded that, in overall, children with malocclusions showed a negative impact on their OHRQoL. The association combined different age groups (from 1‐ to 5‐year‐old group to 11‐ to 17‐year‐old group of participants) and the use of different OHRQoL instruments, however.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the occlusal traits, we observed that the increased overjet had a negative impact on the quality of life of 5‐year‐old children independent of the presence of remaining clinical and demographic variables. A recent systematic review concluded that, in overall, children with malocclusions showed a negative impact on their OHRQoL. The association combined different age groups (from 1‐ to 5‐year‐old group to 11‐ to 17‐year‐old group of participants) and the use of different OHRQoL instruments, however.…”
Section: Discussionmentioning
confidence: 99%
“…Scarce evidence is available from self-reports of five-year-old children, however 8 . On the other hand, a recent systematic review did not associate malocclusions and the OHRQoL of preschool children measured by proxy reports 14 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…observed that the children between the age of 11 and 14 years were more likely to show impact of malocclusion on OHRQOL as compared to younger age group. [5]…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a recent meta-analysis showed that the association between objective orthodontic treatment need assessed with the DAI and OHRQoL is highly heterogeneous, whereas this association assessed with the IOTN is not. 28 Finally, like in every observational study, our study findings might be affected by residual confounding, although we were able to minimize confounding of the study findings by constructing fully adjusted models including indicators for socioeconomic status and objective orthodontic treatment need.…”
Section: Discussionmentioning
confidence: 95%